ChemInform Abstract: Synthesis, Antiproliferative and Apoptosis‐Inducing Activity of Thiazolo[5, 4‐d]pyrimidines. Issue 20 (20th May 2014) - Singh, Baljinder; Guru, Santosh K.; Kour, Smit; Jain, Shreyans K.; Sharma, Rajni; Sharma, Parduman R.; Singh, Shashank K.; Bhushan, Shashi; Bharate, Sandip B.; Vishwakarma, Ram A.
Abstract 14 Title compounds of type (V) are prepared and tested for their antiproliferative and apoptosis‐inducing activities.